The endocannabinoid system as a possible target to treat both the cognitive and emotional features of post-traumatic stress disorder (PTSD) - Trezza, Viviana; Campolongo, Patrizia (Frontiers in Behavioral Neuroscience, 2013)
Posttraumatic stress disorder (PTSD) is a psychiatric disorder of significant prevalence and morbidity, whose pathogenesis relies on paradoxical changes of emotional memory processing. An ideal treatment would be a drug able to block the pathological over-consolidation and continuous retrieval of the traumatic event, while enhancing its extinction and reducing the anxiety symptoms. While the latter benefit from antidepressant medications, no drug is available to control the cognitive symptomatology. Endocannabinoids regulate affective states and participate in memory consolidation, retrieval and extinction. Clinical findings showing a relationship between Cannabis use and PTSD, as well as changes in endocannabinoid activity in PTSD patients, further suggest the existence of a link between endocannabinoids and maladaptive brain changes after trauma exposure. Along these lines, we suggest that endocannabinoid degradation inhibitors may be an ideal therapeutic approach to simultaneously treat the emotional and cognitive features of PTSD, avoiding the unwanted psychotropic effects of compounds directly binding cannabinoid receptors.